2008
DOI: 10.4161/oxim.1.1.6694
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Chronic Nicotinamide Treatment after Traumatic Brain Injury Can Alter Components of Functional Recovery Independent of Histological Damage

Abstract: Previously, we have shown that the window of opportunity for nicotinamide (NAM) therapy (50 mg/kg) following cortical contusion injuries (CCI) extended to 4–8 hrs post-CCI when administered over a six day post-CCI interval. The purpose of the present study was to determine if a more chronic NAM treatment protocol administered following CCI would extend the current window of opportunity for effective treatment onset. Groups of rats received either unilateral CCI's or sham procedures. Initiation of NAM therapy (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
59
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(68 citation statements)
references
References 35 publications
6
59
3
Order By: Relevance
“…13,[42][43][44] To assess sensory deficits, this test was administered on Days 4,6,8,11,17,24, and 28 post-injury. Rats were pre-tested for baseline levels on the two days prior to surgery.…”
Section: Sensory Assessment: Bilateral Tactile Adhesive Removal Taskmentioning
confidence: 99%
See 2 more Smart Citations
“…13,[42][43][44] To assess sensory deficits, this test was administered on Days 4,6,8,11,17,24, and 28 post-injury. Rats were pre-tested for baseline levels on the two days prior to surgery.…”
Section: Sensory Assessment: Bilateral Tactile Adhesive Removal Taskmentioning
confidence: 99%
“…We have reliably shown that this technique is sensitive enough to detect treatment-induced reductions in injury size. 6,9,13,47 Inter-rater reliability scores were calculated for approximately 25% of the data collected. Data were chosen randomly and the criterion for acceptance was a correlation coefficient of r > 0.90.…”
Section: Lesion Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Much work has demonstrated that treatment with nicotinamide significantly reduced injury volume, decreased glial fibrillary acidic protein (GFAP) + activation, reduced blood-brain barrier (BBB) breach, reduced acute edema formation, improved motor performance, and generally reduced behavioral impairments and improved outcomes following cortical contusion injury (CCI) and fluid percussion injury (FPI). [4][5][6][7][8][9][10][11][12] Direct comparisons between a 50 mg/kg and a 500 mg/kg dosing regimen have resulted in some minor dose differences, but in general, both dosing regimens have been shown to be effective in facilitating recovery of function following FPI. 9 More importantly, we have also shown that the window of opportunity for the 50 mg/kg dose is between 6 and 24 h post-CCI, depending upon the task and treatment regimen.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12] Direct comparisons between a 50 mg/kg and a 500 mg/kg dosing regimen have resulted in some minor dose differences, but in general, both dosing regimens have been shown to be effective in facilitating recovery of function following FPI. 9 More importantly, we have also shown that the window of opportunity for the 50 mg/kg dose is between 6 and 24 h post-CCI, depending upon the task and treatment regimen. 7,8 Therefore, there is substantial pre-clinical evidence in young animals (3-6 months) that nicotinamide significantly improves functional recovery and reduces many pathophysiological variables following TBI.…”
Section: Introductionmentioning
confidence: 99%